Association between the atherogenic index of plasma and major adverse cardiovascular events in patients with premature coronary artery disease - Xiangzhen Ran; Zhenguo Wu; Dachuan Guo; Shuai Zhang; Li Liu; Sha Chen; Chunfei Song; Cheng Zhang; Jianmin Yang (European Journal of Medical Research)
Abstract Background The atherogenic index of plasma (AIP) as a novel lipid biomarker has been shown to be an important predictor of atherosclerosis and coronary artery disease. However, it remains unclear whether AIP has prognostic value for patients with premature coronary artery disease (PCAD). Therefore, the present investigation aims to explore the relationship between AIP and major adverse cardiovascular events (MACE) in the PCAD population. Methods A total of 721 patients with PCAD diagnosed by coronary angiography were enrolled in this study. Their AIP was calculated as log [triglyceride (TG)/high-density lipoprotein-cholesterol (HDL-C)]. The primary outcome of this study was MACE, defined as a combination of cardiovascular (CV) death, coronary artery revascularization, non-fatal myocardial infarction (MI), and non-fatal stroke. Results After a median follow-up time of 52 months, 138 patients developed MACE. The patients in the highest AIP tertile group have a higher incidence of MACE (26.6% vs 11.8% and 19.8%, p < 0.001). The Kaplan–Meier curves demonstrated that there were significant differences in the risk of MACE among different AIP groups (log-rank p < 0.001). In addition, the multivariable Cox regression model showed that the hazard ratio of MACE in the highest tertile group was 2.27 (95% CI 1.30–3.94), and 1.33 (95% CI 1.06–1.67) for per SD increase in AIP. Conclusions AIP is significantly associated with the risk of MACE in patients with PCAD and serves as a novel independent prognostic marker for this population.